Commercialization of scientific and technical researches of universitiees - Matviy, Solomiya; Korol, Yaroslaw (Видавництво Львівської політехніки, 2017)
The main directions of commercialization of scientific and technical researches of universities in the world and domestic market of educational services are considered (in particular, on the example of Lviv Polytechnic); the main problems of the development of university science and the ways of their solution both at the national and regional levels, and at the level of individual universities.
Keywords: scientific and technical research; commercialization of science; university; scientific potential; cooperation